The replication and reduction of automobility: findings from Aotearoa, New Zealand - Hopkins, D; Stephenson, J (Elsevier, 2016)
In this paper, we examine the factors that contribute to the replication or reduction of automobility amongst young adults. Semi-structured interviews conducted in Aotearoa New Zealand, with 51 drivers and non-drivers, aged 18-35 years old, form the empirical material. The findings build upon previous research and extend understandings of how seven explanatory factors; perceptual, value and preference, social, built environment, economic, legal/ policy and technological, work both to continue the current automobility paradigm, and to challenge it by adopting alternative mobilities. We use the Energy Cultures Framework as an analytical tool to explore the ways through which material factors, norms, practices, and external context can replicate or reduce participation in the hegemonic mobility paradigm. This approach offers useful insights into the interactions between what the research participants think, have and do, and how this is resulting in a reduction in automobility norms amongst some younger people. It also identifies and highlights potential opportunities to leverage upon current change trends to assist a systemic transition away from automobility towards a culture of multi-mobilities.